First experience with Tolvaptan for the treatment of neonates and infants with capillary leak syndrome after cardiac surgery - Anne Kerling; Okan Toka; André Rüffer; Hanna Müller; Sheeraz Habash; Christel Weiss; Sven Dittrich; Julia Moosmann (BMC, 2019)
Abstract Background Postoperative fluid management in critically ill neonates and infants with capillary leak syndrome (CLS) and extensive volume overload after cardiac surgery on cardiopulmonary bypass is challenging. CLS is often resistant to conventional diuretic therapy, aggravating the course of weaning from invasive ventilation, increasing length of stay on ICU and morbidity and mortality. Methods Tolvaptan (TLV, vasopressin type 2 receptor antagonist) was used as an additive diuretic in neonates and infants with CLS after cardiac surgery. Retrospective analysis of 25 patients with CLS including preoperative and postoperative parameters was performed. Multivariate regression analysis was performed to identify predictors for TLV response. Results Multivariate analysis identified urinary output during 24 h after TLV administration and mean blood pressure (BP) on day 2 of TLV treatment as predictors for TLV response (AUC = 0.956). Responder showed greater weight reduction (p < 0.0001), earlier weaning from ventilator during TLV (p = 0.0421) and shorter time in the ICU after TLV treatment (p = 0.0155). Serum sodium and serum osmolality increased significantly over time in all patients treated with TLV. Conclusion In neonates and infants with diuretic-refractory CLS after cardiac surgery, additional aquaretic therapy with TLV showed an increase in urinary output and reduction in bodyweight in patients classified as TLV responder. Increase in urinary output and mean BP on day 2 of treatment were strong predictors for TLV response.